Wybrane zagadnienia projektowania mobilnego dostępu do zasobów wiedzy - Pawełoszek-Korek, Ilona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper takes up the subject of mobile access to corporate knowledge resources. Knowledge resources are stored as electronic documents in company's databases and archives. Mobile workers are people who do their work away from company's headquarters. Many times they need information from company's knowledge resources, which is not directly accessible for them. The paper presents guidelines for designing mobile access to corporate knowledge resources. The paper also presents the problem of usability verification of mobile applications. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 350-363